2013
DOI: 10.1159/000352090
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Lymph Node Status in Early-Stage Breast Cancer Patients with Sentinel Node Micrometastases (0.2-2 mm)

Abstract: Background: Omission of axillary lymph node dissection (ALND) is increasingly becoming the new standard of care for patients with sentinel lymph node micrometastases (SNMMs). However, a formidable proportion of patients is afflicted with non-sentinel node (NSN) macrometastatic tumor burden. Methods: Over 1 decade 5,000 patients underwent sentinel node biopsies (SNB) at 2 certified breast cancer centers in Austria. All available cases of SNMM during this time period were reviewed. Clinical, tumor and lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…It is noted that several studies have reported the specific situation of SLN examination and the number of micrometastases, and some studies included ITC in their analysis. In this study, 54.1% of the patients had one to two SLNs removed, which was similar to previous research [ 26 , 30 , 36 ]. Moreover, the median and range of SLNs in our study were also consistent with previous research [ 17 , 24 , 26 , 27 , 29 , 30 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It is noted that several studies have reported the specific situation of SLN examination and the number of micrometastases, and some studies included ITC in their analysis. In this study, 54.1% of the patients had one to two SLNs removed, which was similar to previous research [ 26 , 30 , 36 ]. Moreover, the median and range of SLNs in our study were also consistent with previous research [ 17 , 24 , 26 , 27 , 29 , 30 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 54.1% of the patients had one to two SLNs removed, which was similar to previous research [ 26 , 30 , 36 ]. Moreover, the median and range of SLNs in our study were also consistent with previous research [ 17 , 24 , 26 , 27 , 29 , 30 , 36 ]. However, two studies showed both a higher median number and wider range [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations